Dry sliding wear behaviour of in-situ fabricated TiC particulate reinforced AA6061 aluminium alloy. (2nd January 2019) - David Raja Selvam, J.; Dinaharan, I.; Rai, Rajakumar S.; Mashinini, P. M.
ABSTRACT: Aluminium alloy AA6061 reinforced with different mass fractions of (0, 2.5, 5, 7.5 & 10 weight percentage) TiC particles was fabricated by the in-situ reaction process. The in-situ synthesized aluminium matrix composite (AMCs) were examined using X-ray diffraction, field emission scanning electron microscope and electron backscatter diffraction. The results from the aforesaid tests revealed the formation of TiC particles. The in-situ formed particles were found to have a homogenous distribution, clear bonding and good interface with the aluminium alloy AA6061. The dry sliding wear test results revealed an improvement in wear performance of aluminium alloy AA6061 due to the presence of TiC particulate. Furthermore, the in-situ formed TiC particulates refined the grain structure. The in-situ formed TiC particles improved the load bearing ability of the AMCs. The wear mechanisms recorded during the wear test were ploughing and adhesion at lower load and delamination at higher load.